Gut microbial signatures and cardiac-microbiota axis in Yili horses with divergent exercise-induced cardiac remodeling - Bao, Yike; Wang, Tongliang; Adina, Wusiman; Yao, Runchen; Chu, Hongzhong; Yao, Xinkui; Meng, Jun; Wang, Jianwen; Ren, Wanlu; Zeng, Yaqi (Frontiers in Microbiology, 2025)
This study aimed to investigate how different training outcomes affect the gut microbiota composition in racehorses. Twenty-six Yili horses underwent a 9-month conditioning training regimen under uniform husbandry and management conditions. Post-training, the horses were divided into an excellence group (D. Y group) and a general group (D. P group) based on their athletic performance, with the top 10 performers constituting the D. Y group and the bottom 10 the D. P group. Cardiac morphology and function were quantitatively assessed via echocardiography, and metagenomic sequencing was performed on fresh fecal samples. Results indicated that there were no significant differences in gut microbiota and echocardiographic parameters between the two groups prior to training. However, significant differences were observed post-training (p < 0.05). At the genus level, Parabacteroides, Bacteroides, and Prevotella exhibited significantly greater abundance n the D. Y group. LEfSe analysis showed that Prevotella was markedly enriched in the D. Y group (LDA > 4). Functional profiling indicated that multiple metabolic pathways were significantly enriched in global and overview maps, with map00534 and map00190 being particularly enriched in the D. Y group (LDA > 2). Within CAZymes genes, eight were significantly enriched in the D. Y group, including four glycoside hydrolase genes, two carbohydrate esterase genes, and two carbohydrate-binding module genes. Echocardiography revealed significant differences in seven parameters between the groups, with the D. Y group exhibiting notably higher LV_MASS_I and LVM values (p < 0.01). dbRDA analysis demonstrated a significant association between LV_MASS_I and LVM and the gut microbiota profile (p < 0.01). These findings suggest that training-induced cardiac remodeling, particularly the increase in LV_MASS_I and LVM, is closely related to alterations in gut microbiota, with Prevotella enrichment potentially serving as a marker of favorable adaptation to the training regimen. The study provides robust evidence for understanding the interaction between aerobic training, gut microbiota, and cardiac characteristics in racehorses, and highlights potential directions for optimizing athletic performance and probiotic strategies in equine athletes.